ANALISIS DAN SIMULASI KECEPATAN LALU-LINTAS PADA SIMPANG JALAN MENGGUNAKAN PERANGKAT LUNAK PTV VISSIM STUDENT VERSION (STUDI KASUS: SIMPANG BERGOTA, KOTA SEMARANG) - Harahap, Ryan Hasnan; Haryadi, Bambang (DAS Institute, 2023)
One of the intersections that has a significant role in the city of Semarang is the Bergota Intersection. The level of traffic density and crowds at this point of the road is quite significant because it is a route from Jalan Pandanaran and towards the Central Java Regional Police, which passes Jalan Kyai Saleh—a transportation movement system of various types and characteristics of the traffic that occurs. The method used in this study is observation by collecting data as input at PTV Vissim, such as geometric data at intersections, vehicle routes, composition, vehicle volume, vehicle speed, and traffic time cycle using the Traffic Counting method at Bergota Intersections based on analysis of recorded results. The drone video then enumerates the traffic flow by counting the vehicles passing through the survey point. Modeling and simulation results using PTV Vissim in the existing conditions at 11:10-11:20 at the Bergota Intersection using vehicle volume data taken from the field show that the highest speed is 20.27 Km/hour on Jalan Minister Supeno. The lowest speed is 14.59 km/hour on Jalan Kyai Saleh Bergota. Modeling and simulation results using PTV Vissim in the existing conditions at 11.10-11.20 Simpang Bergota using vehicle volume data taken from the field show that the highest delay is 41.19 seconds on Jalan Kyai Saleh Bergota - Jalan Kyai Saleh Veteran. At the same time, the lowest delay is 5.59 seconds on Jalan Dr. Kariadi – Jalan Kyai Saleh Bergota.